(untitled) - Sue, Marsha Petrie (Hoboken, N.J., 2007)
From corporate America to the smallest business owner, this book should be mandatory reading because it provides toxic relief that will put money in your pocket and calm in your personality. A dose of this reading would enhance the success of business school students and smooth out a few bumps in a rocky marriage
Keywords: Conflict management,Interpersonal relations,Interpersonal conflict,Quản lý xung đột,Quan hệ giữa các cá nhân